113k views
1 vote
Given that the quadratic equation has equal roots (k^2-1)x^2-2kx-3k-1=0

Show that 3k^3-3k-1=0​

User Loulou
by
5.0k points

1 Answer

2 votes

Answer:

(See explanation for further details)

Explanation:

The real expression is:


(k^(2)-1)\cdot x{{2} - 2\cdot k \cdot x - 3\cdot k + 1 = 0

The general equation for the second-order polynomial is:


x = \frac{2\cdot k \pm \sqrt{4\cdot k^(2)-4\cdot (k^(2)-1)\cdot (-3\cdot k + 1)}}{k^(2)-1}

This condition must be observed for the case of a quadratic equation with equal roots:


4\cdot k^(2) - 4\cdot (k^(2)-1)\cdot (-3\cdot k + 1) = 0


k^(2) + (k^(2)-1)\cdot (3\cdot k + 1) = 0


k^(2) + 3\cdot k^(3) - 3\cdot k - k^(2)-1 = 0


3\cdot k^(3) - 3\cdot k - 1 = 0

User Ismaran Duwadi
by
5.3k points